2021
DOI: 10.1097/bpb.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis under different treatment in children with developmental dysplasia of the hip: a network meta-analysis

Abstract: The objective of this study was to evaluate the incidence of avascular necrosis (AVN) of the femoral head in children less than 3 years of age with developmental dysplasia of the hip (DDH) treated with closed reduction, open reduction alone and open reduction combined with osteotomy. We reviewed clinical trials from the PubMed, EMBASE and Cochrane Library databases (up to November 2020) that were related to closed reduction, open reduction alone and open reduction combined with osteotomy for the treatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The condition might result from traumatic or non-traumatic factors and eventually leads to the collapse of the femoral head [ 1 , 23 , 24 ]. Furthermore, AVN of the femoral head is linked to pathological synovial reaction, hypertrophy, effusion, and an increase in intra-articular pressure [ 2 , 4 , 25 28 ]. To understand the correlation between intra-articular pressure of the hip joint and blood flow to the femoral head in animal models, a microsphere of radioactively-labeled red cells was used.…”
Section: Discussionmentioning
confidence: 99%
“…The condition might result from traumatic or non-traumatic factors and eventually leads to the collapse of the femoral head [ 1 , 23 , 24 ]. Furthermore, AVN of the femoral head is linked to pathological synovial reaction, hypertrophy, effusion, and an increase in intra-articular pressure [ 2 , 4 , 25 28 ]. To understand the correlation between intra-articular pressure of the hip joint and blood flow to the femoral head in animal models, a microsphere of radioactively-labeled red cells was used.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated via multivariate analysis that closed reduction and open reduction had comparable effects on the incidence of osteonecrosis. For children under 3 years old with DDH, open reduction alone is most likely to be the treatment with the highest incidence rate of ANFH, followed by open reduction combined with osteotomy, and closed reduction is the least likely to cause ANFH ( 14 ), suggesting that the association of DDH classification and preoperative traction with the risk of ANFH may vary in DDH patients with closed and open reduction. Then we explored this potential variation across closed and open reduction populations, and demonstrated that for children undergoing open reduction, DDH classification was positively associated with the risk of postoperative ANFH, and those with preoperative traction had a lower risk of postoperative ANFH than those without.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above with small sample sizes, the associations between the identified risk factors and ANFH may vary in DDH patients with different ages. Besides, sex and surgical method (closed and open reduction), relating to the risk of ANFH ( 8 , 14 ), should also be considered when evaluating the risk factors of ANFH, which lacks research at present.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Additional data also suggest that patients who undergo open reduction alone are at increased risk for proximal femoral growth disturbance (PFGD) (often termed avascular necrosis) and reoperation. 5,8 Nevertheless, assessment of preoperative and intraoperative risk factors for complications after open reductions has been limited to smaller, single-center cohorts.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated that clinical outcomes after open hip reduction are better for younger patients and those treated with concomitant pelvic osteotomy 5–7. Additional data also suggest that patients who undergo open reduction alone are at increased risk for proximal femoral growth disturbance (PFGD) (often termed avascular necrosis) and reoperation 5,8. Nevertheless, assessment of preoperative and intraoperative risk factors for complications after open reductions has been limited to smaller, single-center cohorts.…”
mentioning
confidence: 99%